Bacteria Associated With Health-Care Acquired Infections from Two Selected Hospitals in Kano Nigeria - Bale, S.I.; Mukhtar, M.D.; Rufa’i, F.A. (International Journal of Scientific Research in Biological Sciences, 2022)
Health-Care acquired infections cause menace to public health most especially the missed potentials among them which tends to be resisting the activity of therapeutic drugs used against them and in spite, causes greater menace to the integrity of the health and in turn burden the quality of life leading to high morbidity and morbidity rate. A sum of 150 samples of wound, urine and blood were obtained from patients with a clinical evidence of Health-Care acquired infections as described by NNIS. The entire sample were cultured on their respective culture media and then passed for biochemical tests, followed by Antibiotics susceptibility testing using disk diffusion method according to the guideline of the Clinical Laboratory Standard Institute. We found that, Gram-positive cocci namely S. aureus, Strep sp. and CoNS were the bacteria associated with Health care acquired infections. Wound swab site tends to be the most frequent site of infection with S. aureus as the most predominant species. However, Gram-positive were found to be resistant to cefuroxime while Gram-negative were sensitive to Cefoxitin with Imipinem having the highest activities against all the bacteria.